THE EFFECT OF INTEREST RATES, THE LEVEL OF COMPETITIVENESS ON FOREIGN EXCHANGE RESERVES IN EMERGING MARKET COUNTRIES IN 2020-2023 WITH THE COVID-19 PANDEMIC AS A DUMMY VARIABLE, FACULTY OF ECONOMICS, UNIVERSITAS NEGERI JAKARTA - Putri, Rananda Elliza; Nikensari, Sri Indah; Sebayang, Karuniana Dianta A. (Yayasan Education and Social Center, 2024)
This study aims to determine the effect of interest rate, competitiveness and covid-19 Pandemic on emerging market Foreign Exchange Reserves. The research method used in this study is a quantitative approach. The data used in this study are panel data from the seventeen countries in emerging market from 2020 to 2023 which are collected through documentation techniques. The test result show that the variables of interest rate, competitiveness have a positive and significant effect on emerging market foreign exchange reserves. Meanwhile, covid-19 pandemic variable has a significant negative effect on emerging market foreign exchange reserves. Simultaneously, all research variables have a significant effect on emerging market foreign exchange reserves. The coefficient of determination test in this study shows a 65% influence on foreign exchange reserves and the remaining 35% in explained by other variables outside the study